Gender and the First World War
XI, 265 p.
Keywords: The First World War cannot be sufficiently documented and understood without considering the analytical category of gender. This exciting volume examines key issues in this area, including the 'home front' and battlefront, violence, pacifism, citizenship and emphasizes the relevance of gender within the expanding field of First World War Studies.